Hannah Arendt: por uma ética dos começos - Morello, Eduardo (2021)
This thesis aims to examine the Arendtian notion of natality, from which it is considered that beings capable of beginning are also capable of containing and resisting to the growing expansion of the desert – worldlessness – and the threat of new “sandstorms” – totalitarian movements. For that, it is worth asking: may the new beginnings still transform the desert into a common and plural world, without the support of the old standards of behavior and the criteria of moral judgment? In response, we seek to examine, based on the Arendtian notion of natality, where the “miracle” of each new beginning is rooted onthologically, the fact the beings capable of beginning at birth are equally capable of creating patterns of behavior and moral judgment inspired and guided by the amor mundi. This act requires the constant exercise of storytelling, the “wisdom of uncertainty” and the “training of one’s own imagination so that it may ‘go out on a visit’”. We call it all an ethic of beginnings. In order to avoid misunderstandings, we also clarify that “an ethics of beginnings” is not a catchphrase or a slogan, nor it is intended to be an ethical theory, nor a trademark, it is just a way of designating one among so many possible ways to relating to the world and with each new life/coming, in order to highlight centrality of birth – of natality – and not of death – of mortality –, while inspired and guided by amor mundi. It is, therefore, a way of relating to the world and its beginnings, inspired and guided by love for the world, which demands the ethics of taking responsibility for it, even if we are always under the danger of the increasing expansion of the desert and under the the threat of new “sandstorms”, because, after all, the world is the space between which we always share, whether we like it or not, with the paradoxical plurality of singular beings.